Synthesis and In Vitro Analysis of 1‐Deoxysphingolipid Ceramide Analogues via UGI Reaction as Potential Anti‐cancer Agents. Issue 2 (14th January 2022) - Kaur, Parleen; Sihag, Swati; Chauhan, Monika; Dhingra, Neelima; Agnihotri, Navneet; Kaur, Ramandeep; Singh, Vasundhara
Abstract: In the present work, a small library of few 1‐deoxysphingolipid ceramides has been designed and synthesized via an efficient UGI multicomponent reaction. The deoxy sphingosine intermediate (10 ) synthesized via Grignard reaction and olefin metathesis reaction was used as the amine component with cyclohexyl isocyanide and various aldehydes. The butyric acid has been used as an acid component which may turn out be an advantage due to the chemo preventive properties of the acid formed after the partial hydrolysis of the ceramide. Compounds (1 ‐6 ) has been synthesised via a short and facile route in high purity and yield. Molecular docking of all the analogues has been carried out with protein Sphingosine Kinase I using BiopredictaVlife MDS tool to determine the relative docking score and ligand‐protein interactions. Further in vitro studies were performed on PC‐3 (prostate cancer) and HCT‐116 (colon cancer) cell lines in which four compounds (1 ‐4 ) showed reasonable anti‐cancer activity against both the cell lines while compound (3 ) showed highest activity with IC50 value of 0.344 μM against PC‐3 (prostate cancer) cell lines and 0.624 μM against HCT‐116 (colon cancer) cell lines. Compound (4 ) showed IC50 value of 0.472 μM against HCT‐116 (colon cancer) cell lines. Abstract : The work illustrates the novel synthesis of deoxysphingolipid bis‐amidic ceramides via one pot Ugi‐4CR multi‐component reaction. Synthesis of a small library of compounds (1 ‐6 ) has been achieved in high purity and yield using butyric acid as an acid component due to its chemo preventive properties, cyclohexyl isocyanide as isocyanate component and different varying different electron withdrawing and electron donating aldehydes as an oxo component. The in‐vitro biological evaluation on PC‐3 cell lines and HCT‐116 cell lines have been done.